2020
DOI: 10.1155/2020/7901231
|View full text |Cite
|
Sign up to set email alerts
|

Jiawei Xianglian Decoction (JWXLD), a Traditional Chinese Medicine (TCM), Alleviates CPT‐11‐Induced Diarrhea in Mice

Abstract: Irinotecan (CPT-11) is used for therapy of various cancers. However, it has several serious adverse reactions such as diarrhea which is caused by SN-38, the active form of CPT-11. This study aimed to evaluate the effectiveness of Jiawei xianglian decoction (JWXLD), which has been widely used for the treatment of diarrhea in China. In this study, a mouse model with delayed diarrhea was generated by CPT-11. Real-time PCR and enzyme-linked immunosorbent assay (ELISA) were performed to explore intestinal microflor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Pro-inflammatory cytokines such as IL-6 and TNF-α are associated with tissue damage ( Hernández-Rodríguez et al., 2004 ). Evidence suggests that the inhibition of pro-inflammatory cytokines (IL-1, IL-6, and TNF-α) supports the protective effect of Jiawei Xianglian Decoction on diarrhea induced by irinotecan ( Lu et al., 2020 ). In the diarrhea piglets model induced by E. coli , the results showed that L. plantarum ZLP001 could significantly inhibit the increase of intestinal permeability induced by E. coli , reduce the expression levels of IL-6 , IL-8 , and TNF-α , and prevent the increase of tight-junction protein expression ( Wang et al., 2018 ).…”
Section: Probiotics and Intestinal Diseases Of Monogastric Animalsmentioning
confidence: 94%
“…Pro-inflammatory cytokines such as IL-6 and TNF-α are associated with tissue damage ( Hernández-Rodríguez et al., 2004 ). Evidence suggests that the inhibition of pro-inflammatory cytokines (IL-1, IL-6, and TNF-α) supports the protective effect of Jiawei Xianglian Decoction on diarrhea induced by irinotecan ( Lu et al., 2020 ). In the diarrhea piglets model induced by E. coli , the results showed that L. plantarum ZLP001 could significantly inhibit the increase of intestinal permeability induced by E. coli , reduce the expression levels of IL-6 , IL-8 , and TNF-α , and prevent the increase of tight-junction protein expression ( Wang et al., 2018 ).…”
Section: Probiotics and Intestinal Diseases Of Monogastric Animalsmentioning
confidence: 94%
“…CPT‐11 is widely used in malignant chemotherapy, but delayed diarrhea, one of its dose‐limiting toxic reactions, causes patients unable to tolerate treatment of CPT‐11 and seriously affects the course of chemotherapy (Bailly, 2019; Kweekel et al, 2008). The clinical application of traditional Chinese medicine (TCM) to prevent and treat CPT‐11‐triggered delayed diarrhea is of great importance (Lu et al, 2020; Wang et al, 2011; Yue et al, 2021). Therefore, the mechanism of the prevention and treatment of CPT‐11‐caused late‐onset diarrhea using TCM required more rigorous and reliable researches, and the relevant target genes and target proteins need to be unveiled.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it can effectively inhibit CPT-11-induced multiplication and differentiation of multiple inflammatory markers and alleviate CPT-11 chemotherapy-induced diarrhea ( 12 ). In addition, some monomers and active ingredients in SBWGR, such as Muxiang and hesperidin, have also been shown to reduce the expressions of some inflammatory factors (e.g., TNF-α) and inhibit the apoptosis of intestinal epithelial cells, thus alleviating the toxic damage of CPT-11 to the intestinal tract ( 13 ).…”
Section: Discussionmentioning
confidence: 99%